Profile of laryngeal cancer patients attended in hospitals of high oncological complexity of Pará in the time series 2000-2017 (Research, Society and Development, 2021)
Objective: To trace the profile of patients with primary laryngeal neoplasia in hospitals of high oncological complexity in Pará in the time series 2000-2017. Method: Retrospective epidemiological study conducted with the secondary database from the Hospital Cancer Registry (RHC). Results: the profile of patients with malignant laryngeal neoplasia in services of high oncological complexity in the state of Pará are mostly: male, over 40, history of alcoholism and/or smoking, white or brown, incomplete elementary school, diagnosed in the most advanced stages advanced. Conclusion: Thus, it is clear that this neoplasm is strongly based on the interaction of environmental and endogenous factors. Above all, the health system is still tenuous to serve patients at risk or with laryngeal neoplasia, starting with the high levels of ignorance present in the secondary databases on health indicators, which implies the tendency of certain important variables for cancer prediction.